Pemberdayaan Pekerja Migran Indonesia Melalui Peningkatan Literasi Kesehatan Herbal Berbasis Komunitas di Selangor, Malaysia - Haryoto Haryoto; Agustono Wibowo; Ahmad Fauzi; Muhtadi Muhtadi; Andi Suhendi; Aditya Naova Sofyan (Altifani Journal: International Journal of Community Engagement, 2026)
Indonesian Migrant Workers (PMI) in Shah Alam, Selangor, Malaysia, face limited access to formal healthcare services, thus heavily relying on herbal-based traditional medicine. Low literacy regarding the safe use of herbs potentially leads to misuse and negative interactions with modern medicine. This International Partnership Community Service (PkM-KI) activity aims to increase the knowledge and awareness of PMI and the community around the surau (Islamic prayer room) regarding the rational and evidence-based use of traditional medicine through a community-based educational approach. The program was conducted over three days through workshops, focus group discussions, and the distribution of bilingual Malay–Indonesian educational booklets containing an introduction to local medicinal plants, proper usage methods, and herbal safety aspects. The evaluation involved 24 respondents using a pre-test and post-test design to measure changes in participants' knowledge levels. Statistical analysis using the paired t-test revealed a highly significant increase in knowledge (p < 0.05), rising from 45.7% before the activity to 97.5% after the intervention. These findings indicate that the surau-based educational approach is effective as a contextual and sustainable medium for disseminating herbal health literacy. This activity not only strengthens PMI's understanding of safe traditional medicine use but also encourages the integration of local wisdom with modern pharmaceutical approaches. This program has the potential to serve as a cross-border community service model for improving herbal-based health literacy among migrant communities and local societies.